2022
DOI: 10.12911/22998993/147808
|View full text |Cite
|
Sign up to set email alerts
|

Set of Suffosion Holes Occurring After a Water Supply Failure as a Structure with Fractal Features

Abstract: As a result of a buried water pipe unsealing, water often flows from the pipe to the soil surface, washing out the solid particles of soil and creating the so-called suffosion holes. It is a dangerous phenomenon, especially in urbanized areas, where it poses a threat to human safety and the stability of infrastructure. Uncontrolled outflows of water from water pipes belong to the main causes of suffosion in cities, occur in all water networks around the world and are difficult to predict. Therefore, it seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…• Approximate self-similarity: This feature has been improved for RSs by enlarging individual frames of the recordings of water outflow and the formation of a suffosion hole [7]. The stages of formation of the suffosion hole were the same regardless of the location of the hole, so it can be concluded that the self-similarity condition is also met by the TLS structure.…”
Section: Results Of Simplifying the Real Structurementioning
confidence: 99%
See 4 more Smart Citations
“…• Approximate self-similarity: This feature has been improved for RSs by enlarging individual frames of the recordings of water outflow and the formation of a suffosion hole [7]. The stages of formation of the suffosion hole were the same regardless of the location of the hole, so it can be concluded that the self-similarity condition is also met by the TLS structure.…”
Section: Results Of Simplifying the Real Structurementioning
confidence: 99%
“…The water outflow locations obtained as a result of laboratory tests created real geometric structures (RSs), which were analyzed in this article. Since it was previously shown that RSs have fractal features [7], the analyses focused on their fractal dimensions (D b ). To simplify the research, an RS was reduced first to a plane form (Theoretical Planar Structure, TPS) and then to a linear form (Theoretical Linear Structure, TLS) using isometric transformations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations